2004
DOI: 10.1016/j.cellbi.2003.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the limits of filopodial sensing: a brief report using SEM to image the interaction between 10 nm high nano‐topography and fibroblast filopodia

Abstract: Having the ability to control cell behaviour would be of great advantage in tissue engineering. One method of gaining control over cell adhesion, proliferation, guidance and differentiation is use of topography. Whilst it has be known for some time that cells can be guided by micro-topography, it is only recently becoming clear that cells will respond strongly to nano-scale topography. The fact that cells will take cues from their micro- and nano-environment suggests that the cells are in some way 'spatially a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
157
0
4

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(171 citation statements)
references
References 37 publications
10
157
0
4
Order By: Relevance
“…Although it can be reasoned that the decrease in adhesion on hex and square may be a result of compromized protein adsorption, or a reduction in surface free energy, a previous study indicates that direct interactions of filopodia with islands down to 10 nm do occur, 38 an indication that mechanotransduction via nanoscale features may be directly associated with cellular ability to gather spatial information. It is, however, probable, considering a cells natural redundancy, that nanotopography affects cellular adhesion via all mechanisms described.…”
Section: Discussionmentioning
confidence: 99%
“…Although it can be reasoned that the decrease in adhesion on hex and square may be a result of compromized protein adsorption, or a reduction in surface free energy, a previous study indicates that direct interactions of filopodia with islands down to 10 nm do occur, 38 an indication that mechanotransduction via nanoscale features may be directly associated with cellular ability to gather spatial information. It is, however, probable, considering a cells natural redundancy, that nanotopography affects cellular adhesion via all mechanisms described.…”
Section: Discussionmentioning
confidence: 99%
“…By observation of osteoblasts using fluorescence microscopy, isotropic nanotopography appeared to have only a little influence on the overall osteoblast shape. Detailed SEM observation by Dalby et al (2004aDalby et al ( , 2004b showed that cells on isotropic nanoscale topography still exhibit unique features. Fluorescence microscopical evaluation of anisotropic nanogrooves on the other hand, affected morphology to much greater extent.…”
Section: Discussionmentioning
confidence: 99%
“…Filopodia have recently been observed to interact with topographic features at the nanoscale level. 16,[59][60][61][62] International Journal of Nanomedicine downloaded from https://www.dovepress.com/ by 34.217.195.47 on 12-May-2018 For personal use only.…”
Section: Discussionmentioning
confidence: 99%